THE ROLE OF BORON COMPOUNDS IN THE FORMATION OF TOURMALINE-GOLD DEPOSITS IN PRIAMURYE - Zimin S.S.; Moiseenko V.G.; Oktyabrskiy R.A.; Tishkin B.M.; Malakhov V.V.; Molchanov V.P. (My University, 2001)
The paper examines the peculiar features of tourmaline-quartz type gold deposits distribution in the earth's crust, as well as its occurrence and principal mineralogical and geochemical features. Presumably, metal borides and boron hydrides of deep-seated mantle levels with reducing regime of mineral formation played a major role in their origin. The former served as major resources of ore matter, while B10H14 boron hydrides reacting with water at high temperature (800-700°C) in the granite melt caused hydrogen generation in according with the reaction B10H14 + 15H2O=5B2O3 + 22H2. In high crust horizons, hydrogen interacts with oxygen at low temperatures (200-100°) to result in water generation followed by abrupt gas pressure drop above magma intrusions. Frequent pressure changes caused by tectonic displacement influencing on gas supply have resulted in disturbance of rocks stability in the main gas channel, to finally form a breccia pipe above the intrusions of granite or kimberlite boron- and hydrogen-bearing magma.